Consequences of Serotonin Transporter Genotype and Early Adversity on Behavioral Profile – Pathology or Adaptation? - Heiming, Rebecca S.; Sachser, Norbert (Frontiers in Neuroscience, 2010)
This review focuses on how behavioral profile is shaped by early adversity in individuals with varying serotonin-transporter (5-HTT) genotype. In a recent study on 5-HTT knockout mice Heiming et al. (2009) simulated a ‘dangerous environment’ by confronting pregnant and lactating females with odor cues of unfamiliar males, indicating the risk of infant killing. Growing up in a dangerous environment induced increased anxiety-related behavior and decreased exploratory locomotion in the offspring, the effects being most pronounced in mice lacking 5-HTT expression. We argue that these alterations in behavioral profile represent adaptive maternal effects that help the individuals to cope with adversity. In principle, such effects of adversity on behavioral profile should not automatically be regarded as pathological. Rather and in accordance with modern evolutionary theory they may represent adaptations, although individuals with 5-HTT genotype induced susceptibility to adversity may be at risk of developing pathologies.